2004
DOI: 10.1029/2003gb002142
|View full text |Cite
|
Sign up to set email alerts
|

Improved estimates of net carbon emissions from land cover change in the tropics for the 1990s

Abstract: [1] Recent figures on net forest cover change rates of the world's tropical forest cover are used for the calculation of carbon fluxes in the global budget. By applying our deforestation findings in the humid tropics, complemented by published deforestation figures in the dry tropics, to refereed data on biomass, we produced new estimates of net carbon emissions. These estimates are supported by recent, independent estimations of net carbon emissions globally, over the Brazilian Amazon, and by observations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
256
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(271 citation statements)
references
References 34 publications
7
256
1
7
Order By: Relevance
“…The analysis does not take account of the following: . An earlier estimate based on high-resolution satellite data over areas identified as 'hot spots' of deforestation, estimated the figure at nearer 3.7 GtCO 2 (1 GtC) for 2000 (Achard et al 2004). It is Houghton's more recent estimate that is used in this paper.…”
Section: Scenario Analysis (A ) Overviewmentioning
confidence: 94%
“…The analysis does not take account of the following: . An earlier estimate based on high-resolution satellite data over areas identified as 'hot spots' of deforestation, estimated the figure at nearer 3.7 GtCO 2 (1 GtC) for 2000 (Achard et al 2004). It is Houghton's more recent estimate that is used in this paper.…”
Section: Scenario Analysis (A ) Overviewmentioning
confidence: 94%
“…Hence, the climate of the Amazon is of particular importance for the fate of global CO 2 concentration in the atmosphere (1). Besides the difficulty of estimating carbon pools (1-3), our incapacity to correctly predict CO 2 fluxes in the continental tropics largely results from inaccurate simulation of the tropical climate (1,2,4,5).…”
mentioning
confidence: 99%
“…In the more humid Western part of the basin, surface incoming radiation, evapotranspiration, and photosynthesis all tend to peak in the dry season (15-17), whereas GCMs simulate peaks of those fluxes in the wet season (10, 11). Those issues might be related to the representation of convection (1,2,4,5,13,14) and vegetation water stress (6)(7)(8)(15)(16)(17) in GCMs.We here show that we can represent the Amazonian climate using a strategy opposite to GCMs in which we resolve convection and parameterize the large-scale circulation (Methods). The simulations lack many of the biases observed in GCMs and more accurately capture the differences between the dry and wet season of the Amazon in surface heat fluxes and precipitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These estimates were much higher than those of Milne and Brown [22], who gave annual sequestration rates of 1.05-1.56 tC/ha for conifers in Britain. At the ecosystem level, Achard et al [23] estimated an average regrowth rate of 2.75 tC ha -1 yr -1 for tropical forests; Van Kooten et al [24] found figures for Canada in the range of 0.6 to 0.8 tC ha -1 yr -1 ; while Brainard et al [25] found that British forests sequestered 3.5 tC ha -1 yr -1 . At the global level, Sedjo and Solomon [26] estimated that forests subtract on average 6.24 tC ha -1 yr -1 , while Nordhaus [27] estimated a range of only 0.8 to 1.6 tC ha -1 yr -1 .…”
Section: Increase In Carbonmentioning
confidence: 99%